Peran Budaya Belajar dalam Membentuk Kemuliaan Santri di Pondok Pesantren Tahfidzul Qur-An Assalam Riyadlul Jannah Bogor - Amaliyah Amaliyah; Khodijah Khodijah (Jurnal PKM Manajemen Bisnis, 2026)
The education system often emphasizes administrative achievements and knowledge transfer, while the internalization of values and character building receives less attention. This issue is also evident in Islamic boarding schools (pesantren), where traditional learning culture plays a crucial role in shaping students’ moral excellence. However, contemporary challenges such as digital disruption and changing learning behavior among Generation Z students have affected traditional learning practices. This Community Service Program (Pengabdian kepada Masyarakat/PKM) aims to strengthen the role of learning culture in shaping the noble character of students at Pondok Pesantren Tahfidzul Qur-An Assalam Riyadlul Jannah, Bogor. The PKM was conducted on May 17, 2026, by two lecturers from Universitas Pamulang, involving 27 participants consisting of teachers and students. The program was implemented through material presentations, discussions, and question-and-answer sessions. The implementation process consisted of three stages: preparation, execution, and reporting. During the implementation stage, participants were introduced to the concept of learning culture, character education, and strategies for strengthening students’ moral values in the digital era. The results of the activity showed increased awareness among participants regarding the importance of maintaining a disciplined learning culture and strengthening Islamic values in daily life. Teachers and students demonstrated active engagement during discussions and showed improved understanding of how learning culture contributes to character formation. Overall, the program successfully reinforced the role of pesantren-based learning culture in fostering students’ moral excellence and adaptability in modern educational contexts.